A Taxonomic Study of the Species Belonging to Metallic Wood Borers(Buprestidae: Coleoptera) in the Syrian Coast - Shiha, Mohammad Salem (Latakia University Journal -Biological Sciences Series, 2013)
Five hundred three specimens of insects related tothe family Buprestidae (Coleoptera) were collected from 34 sites in the Syrian coast during 2009 and 2010.The Morphological and taxonomic aspects of the collected specimens were studied, and thenidentification keys of genera and species were obtained depending on the most importanttaxonomic features. This led to the identification ofsixteen species belonging to nine genera. These are recorded and classified.They are:Perotis (Aurigina) chlorana, Capnodis tenebricosa, Capnodis porosa, Capnodis miliaris, Capnodis cariosa, Capnodis tenebrionis, Capnodis carbonaria, Capnodis henningi, Ptosima undecimmaculata, Chalcophora detrita, Chalcophorella quadrioculataand Chalcophorella stigmatica. The following speciesJulodis andrea, Acmaeodera polita, Anthaxia dimidialaand Buprestis dalmatinaarerecorded for the first time in Syria.